2006
DOI: 10.1111/j.1574-695x.2006.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the major surface epitope of the CopB outer membrane protein ofMoraxella catarrhalis

Abstract: The CopB outer membrane protein has been considered a vaccine candidate for the prevention of infections due to Moraxella catarrhalis. Monoclonal antibody 10F3 recognizes whole cells of about 70% of clinical isolates, suggesting that this epitope is reasonably conserved. To determine whether CopB has other surface epitopes, we analyzed M. catarrhalis isolates using polyclonal sera against recombinant CopB proteins from a 10F3 positive isolate and a 10F3 negative isolate, and polyclonal sera against synthetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…4A). Bovine serum albumin and the purified recombinant CopB protein (rCopB) of M. catarrhalis (23), included as negative controls, did not display affinity to mucin. To assess functional characteristics of the antisera against CD, their effects on the CD-mucin binding activity were examined.…”
Section: Resultsmentioning
confidence: 99%
“…4A). Bovine serum albumin and the purified recombinant CopB protein (rCopB) of M. catarrhalis (23), included as negative controls, did not display affinity to mucin. To assess functional characteristics of the antisera against CD, their effects on the CD-mucin binding activity were examined.…”
Section: Resultsmentioning
confidence: 99%
“…It was possible reason that high degree of identities had the same or more similar epitopes and strongly immune response were induced. It was reported that the degree of sequence identity of CopB affected the polymorphism of the major surface epitopes in Moraxella catarrhalis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Five units of RsaI (copB) or 5 units of BseJI (ompCD) were used per reaction mix, incubated at 37 uC or 65 uC, respectively. The copB PCR RFLP typing method was based upon sequence data published by Liu et al (2006) but cannot distinguish between CopB types I and III (Liu et al, 2006). Expected visible product sizes were: 374 and 157 bp for CopB type 0; 342 and 157 bp for CopB types I/III; 332 and 187 bp for CopB type II; and 519 bp for CopB type IV.…”
mentioning
confidence: 99%